Experimental pathology of local tissue damage induced by Bothrops asper snake venom - Gutiérrez, José María (2009)
Envenomations by Bothrops asper are often associated with complex and severe local pathological manifestations, including edema, blistering, dermonecrosis, myonecrosis and hemorrhage. The pathogenesis of these alterations has been investigated at the experimental level. These effects are mostly the consequence of the direct action of zinc-dependent metalloproteinases (SVMPs) and myotoxic phospholipases A2 (PLA2s). SVMPs induce hemorrhage, blistering, dermonecrosis and general extracellular matrix degradation, whereas PLA2s induce myonecrosis and also affect lymphatic vessels. In addition, the prominent vascular alterations leading to hemorrhage and edema may contribute to ischemia and further tissue necrosis. The mechanisms of action of SVMPs and PLA2s are discussed in detail in this review. Venom-induced tissue damage plays also a role in promoting bacterial infection. A prominent inflammatory reaction develops as a consequence of these local pathological alterations, with the synthesis and release of abundant mediators, resulting in edema and pain. However, whether inflammatory cells and mediators contribute to further tissue damage is not clear at present. Muscle tissue regeneration after venom-induced pathological effects is often impaired, thus resulting in permanent tissue loss and dysfunction. SVMP-induced microvessel damage is likely to be responsible of this poor regenerative outcome. Antivenoms are only partially effective in the neutralization of B. asper-induced local effects, and the search for novel toxin inhibitors represents a potential avenue for improving the treatment of this serious aspect of snakebite envenomation.